“We must be precise” : finding a shape for experience in Julian Barnes’ Flaubert’s parrot, a history of the world in 10½ chapters, and levels of life - Lee, Cheryl Julia (2014)
Julian Barnes’ novels have often been studied within the field of postmodernism and ‘historiographic metafiction’. Coined by Linda Hutcheon, the term refers to “novels which are both intensely self-reflexive and yet paradoxically also lay claim to historical events and personages” (Poetics 5). Although Hutcheon foregrounds the literary text in order to do justice to the “broad contemporary phenomena” (Narcissistic Narrative 2) that is metafiction, she narrows the scope of the novels she discusses by imposing her own critical framework on them. This is a framework developed primarily in opposition to postmodernist theorists such as Frederic Jameson and that is concerned principally with the epistemological status of the past. Analysis grounded in Hutcheon’s ideas tends to end in the recognition of the text’s “theoretical self-awareness of history and fiction as human constructs” (Hutcheon, Poetics 5). This essay contends that Barnes’ fiction however, resists such confinement. Working on Hutcheon’s basic assumption of historiographic metafiction as a genre in which the emphasis is on the literary text, this essay hopes to do for Barnes’ novels what Hutcheon aspired but arguably failed to do for the novels she discusses: to undertake a close investigation of the text’s self-reflexivity without subordinating the novels’ concerns and aesthetic qualities to a theoretical agenda. Specifically, this essay examines the particular treatment of history and its representation in "Flaubert’s Parrot", "A History of the World in 10½ Chapters", and "Levels of Life". In doing so, the essay traces the development of Barnes’ understanding of ‘history’, from a rigid structure to be deconstructed and challenged into a more abstract and fluid shape capable of accommodating the flux of experience.